Comparison of Oral Health-Related Quality Of Life among Adult Referred to Public and Private Dental Clinics of Mashhad, Iran - Zahra Mohammadzadeh; Faezeh Jafarnejad; Taraneh Movahed (Mashhad University of Medical Sciences, 2017)
Introduction: Nowadays, appraisal of patients' perception of health has largely replaced the clinical evaluations. This study aimed to compare oral health-related quality of life in patients referring to public and private clinics in Mashhad, Iran. Materials and Methods: In this cross-sectional study, we enrolled 383 patients referred to five private and two public dental clinics in Mashhad, Iran. The study variables including age, gender, level of education, functional dentition status, decayed, missing, and filled teeth, and the reason for referral were recorded. Oral Impact on Daily Performance (OIDP) score was calculated for each patient. To analyze the data, independent samples t-test, Man-Whitney U test, and Chi-squared test were run. Results: The reason for visiting the public and private clinics was significantly different (P